Atomic Insights into the Enhanced Surface Stability in High Voltage Cathode Materials by Ultrathin Coating. (3rd January 2017) - Fang, Xin; Lin, Feng; Nordlund, Dennis; Mecklenburg, Matthew; Ge, Mingyuan; Rong, Jiepeng; Zhang, Anyi; Shen, Chenfei; Liu, Yihang; Cao, Yu; Doeff, Marca M.; Zhou, Chongwu
Abstract : Surface properties of electrode materials play a critical role in the function of batteries. Therefore, surface modifications, such as coatings, have been widely used to improve battery performance. Understanding how these coatings function to improve battery performance is crucial for both scientific research and applications. In this study the electrochemical performance of coated and uncoated LiNi0.5 Mn1.5 O4 (LNMO) electrodes is correlated with ensemble‐averaged soft X‐ray absorption spectroscopy (XAS) and spatially resolved scanning transmission electron microscopy‐electron energy loss spectroscopy (STEM‐EELS) to illustrate the mechanism of how ultrathin layer Al2 O3 coatings improve the cycle life of LiNi0.5 Mn1.5 O4 . Mn 2+ evolution on the surface is clearly observed in the uncoated sample, which results from the reaction between the electrolytic solution and the surfaces of LiNi0.5 Mn1.5 O4 particles, and also possibly atomic structure reconstructions and oxygen loss from the surface region in LiNi0.5 Mn1.5 O4 . The coating effectively suppresses Mn 2+ evolution and improves the battery performance by decelerating the impedance buildup from the surface passivation. This study demonstrates the importance of combining ensemble‐averaged techniques (e.g., XAS) with localized techniques (e.g., STEM‐EELS), as the latter may yield unrepresentative information due to the limited number of studied particles, and sheds light on the design of future coating processes and materials. Abstract : Atomic layer deposition was employed as an ultrathin coating on LiNi0.5 Mn1.5 O4, a cathode in lithium‐ion batteries. X‐ray absorption spectroscopy and scanning transmission electron microscopy‐electron energy loss spectroscopy were used to characterize both pristine and coated materials before and after cycling. The results show that the coating suppressed Mn 2+ formation, decelarating impedance buildup from surface passivation and improving cycling behavior.